The Effect of Social Media Influencers on Visit Intention in the Restaurant Industry - Bash, Mohamad; Bandyopadhyay, Anupam; Pahari, Munmun Patra; Pahari, Subhajit (Indian Journal of Marketing, 2024)
Purpose : This paper integrated the stimulus–organism–response (S–O–R) framework and media richness theory to investigate the impact of influencers on social media on customers’ visit intention through customer attitude and parasocial relationships. Methodology : The information was gathered via a survey, and 360 answers were included in the final analysis. Structural equation modeling was used to evaluate the relationships among the constructs. Findings : We found that the perceived social media influencers’ (SMIs) credibility and message content dimensions (atheistic and usefulness) increased the followers’ contributed engagement and the intention to visit the endorsed restaurant through parasocial relationships and customer attitude. Furthermore, the media richness of SMI’s posts enhanced the relationship between influencer credibility, aesthetic message content, and followers’ contributed engagement. Practical Implications : When choosing a specific SMI for their promotion strategy, restaurant owners should take into account media richness criteria in addition to influencer credibility, aesthetics, and usefulness posts. Originality : This study combined the S–O–R theory with media richness theory, in contrast to previous influencer literature research, to explain the influencers’ effect on their followers.